2010
DOI: 10.1542/peds.2010-0217
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Decision-Making in Newborn Screening: Opinions, Choices, and Information Needs

Abstract: Participants supported newborn screening for treatable disorders but suggested optional screening for other disorders. The variable influences on parents' decision-making suggest that parents with diverse experiences, if they were included in decision-making regarding screening policies, could provide critical perspectives and help screening programs address parents' preferences and meet parents' information needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 27 publications
4
31
2
Order By: Relevance
“…Several studies have found that having adequate information improved parents' experiences of positive screens. 31,35,37 In our study, such parents recounted confusion and distress, with some having no memory that their child had even been screened. Providing key information well before delivery could help alleviate later distress by preparing parents for the possibility of positive screening results, and reinforcing the difference between screening and diagnosis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Several studies have found that having adequate information improved parents' experiences of positive screens. 31,35,37 In our study, such parents recounted confusion and distress, with some having no memory that their child had even been screened. Providing key information well before delivery could help alleviate later distress by preparing parents for the possibility of positive screening results, and reinforcing the difference between screening and diagnosis.…”
Section: Discussionmentioning
confidence: 80%
“…17,29 Results are consistent with a growing literature revealing very supportive parental views of NBS. 27,29,[35][36] It is important to appreciate that the majority of parents in NBS programs are 'satisfied customers': 37 most will receive screen negative results, and in the case of acceptance of screening, their understanding is not put to the test. It highlights the importance, in research and quality assurance studies, of seeking out those participants who are most likely to provide a discordant view, however infrequent this is.…”
Section: Discussionmentioning
confidence: 99%
“…being included in the review, 8,12,14,15,17,19,20,25,26,[28][29][30]33, covering NBS in a number of different countries: England (n = 11 8,14,25,62,66,70,72,[78][79][80]83 ), Wales (n = 2 85,86 ), France (n = 1 89 ), Germany (n = 1 15 ), the Netherlands (n = 1 29 ), USA (n = 20 17,19,26,30,33,61,63,64,71,[74][75][76]81,82,84,87,88,90,91,93 ), Canada (n = 4 12,65,…”
Section: Theories Of Informed Consent: Developing An Analytical Framementioning
confidence: 99%
“…Although numerous papers focused on parents' information needs, these were sometimes inferred from guidelines or from health professionals' views rather than by asking parents directly. Studies using parent samples found that the following topics were valued: l testing -how this is carried out 14,66,70,76,77 l results -when they are provided and how 14,26,63,70,76,77 l the purpose of screening 62,63,70,77 l choice 14,62,66,70,72 l conditions screened for: 14,70,76 ¢ detailed 76 ¢ basic and implications 12,14 l storage 30,68,77 l treatment 63,70,76 l carriers 29,64,78 l the importance of having a child screened/benefits 62,63 l risks -infections 70,78 l the need for further samples/how to respond if in the USA 26,78 70 l information about the fact that screening uses deoxyribonucleic acid (DNA) 70 l heritability 76 l screening alternatives (e.g. testing later in life) …”
Section: Content Of Relevant Informationmentioning
confidence: 99%
See 1 more Smart Citation